Controle do cupim de montículo (Isoptera: Termitidae) de pastagem com fungos entomopatogênicos - Toscano, Luciana Claudia; Schlick-Souza, Eunice Claudia [UNESP]; Mamore Martins, Gustavo Luis; Souza-Schlick, Genivaldo David [UNESP]; Maruyama, Wilson Itamar (Univ Fed Rural Semi-arido-ufersa, 2010)
The objective of this study was to evaluate the control of mound-building termites (Isoptera: Termitidae) by entomopathogenic fungi (Metarhizium anisopliae and Beauveria bassiana). We developed two experiments, with two copies of application in three sizes of nests. The first was installed in the Salto Macauba farm and second in the Laboratory of Plant Protection at the State University of Mato Grosso do Sul. The first experiment consisted of five repetitions, each nest an experimental unit, with treatments in a factorial 2 (fungi) x 2 (tests) x 2 (type of spraying) + 1 control, distributed completely at random in the area. The treatments were: 1) control - no implementation, 2) Metarril M103 (M. anisopliae) - 10 g/mound-dusting, 3) Metarril M103 - 10 g/mound - via net, 4) Metarril M103 - 15 g/mound-dusting, 5) Metarril M103 - 15 g/mound - via net, 6) Boveril B102 (B. bassiana) - 10 g/mound - dusting, 7) Boveril B102 - 10 g/mound - via net, 8) Boveril B102 - 15 g/mound-dusting and 9) Boveril B102 - 15 g/mound-via net. The testing of mortality were made spraying of the laboratory with the field measurements performed in compliance with the same separation of the nests. The results suggested that the road dust (dosage of 10 g) of the fungi studied showed higher mortality of nests of small size (53%). B. bassiana (Boveril) (10 g) gave 80% mortality of C. cumulans when applied to nests of small size.

O objetivo do trabalho foi avaliar o controle de cupins de montículo (Isoptera: Termitidae) com fungos entomopatogênicos (Metarhizium anisopliae e Beauveria bassiana). Foram desenvolvidos dois experimentos, com duas vias de aplicação (polvilhamento e via líquida) em três tamanhos de cupinzeiros (pequeno, médio e grande). O primeiro foi instalado a campo na Fazenda Salto da Macaúba e o segundo no Laboratório de Fitossanidade da Universidade Estadual de Mato Grosso do Sul. O primeiro experimento constou de cinco repetições, sendo cada cupinzeiro uma unidade experimental, com os tratamentos em esquema fatorial 2 (fungos) x 2 (dosagens) x 2 (tipos de aplicação) + 1 testemunha, distribuídos completamente ao acaso na área. Os tratamentos utilizados foram: 1) testemunha – sem aplicação; 2) M103 (M. anisopliae) - 10g/montículo – polvilhamento; 3) Metarril® M103 - 10g/montículo – via líquida; 4) Metarril ®M103 - 15g/montículo – polvilhamento; 5) Metarril M103 - 15 g/montículo – via líquida; 6) Boveril® B102 (B. bassiana) - 10 g/montículo – polvilhamento; 7) Boveril® B102 - 10 g/montículo – via líquida; 8) Boveril® B102 - 15 g/montículo – polvilhamento e 9) Boveril® B102 - 15 g/montículo – via líquida. Os testes de mortalidade foram realizados com aplicações dos produtos no laboratório com as dosagens realizadas no campo respeitando a mesma separação dos cupinzeiros. Os resultados sugeriram que a via pó (dosagem de 10 g) dos fungos estudados proporcionou maior mortalidade de cupinzeiros de tamanho pequeno (53%). B. bassiana (Boveril) (10 g) proporcionou 80% de mortalidade de Cornitermes cumulans quando aplicado em cupinzeiros de tamanho pequeno.
Control of mound-building termite (Isoptera: Termitidae) of pasture with entomopathogenic fungus
Keywords: Biological control; Cornitermes cumulans; Metarhizium anisopliae; Beauveria bassiana